Similarities and Differences in Health, Social Trust, and Financial Situation in People With Usher Syndrome, a Bio-Psychosocial Perspective - Wahlqvist, Moa; Möller, Claes; Möller, Kerstin; Danermark, Berth (Frontiers in Psychology, 2020)
Purpose: The primary aim was to describe the similarities and differences among the general health, physical health, psychological health, social trust and financial situations of people with Usher syndrome (USH) types 1, 2 and 3. A second aim was to explore whether age, gender, clinical diagnosis, visual field, visual acuity and degree of hearing impairment were associated with the general health, physical health, psychological health, social trust and financial situations of people with USH. Methods: In this study, 162 people with USH living in Sweden were included, and all three types of the disease were represented. Data concerning vision, hearing and genetics were retrieved from the Swedish Usher database. Group comparison using frequencies, χ2-tests and Kruskal Wallis tests for group comparison were used. To examine the effect of independent variables on poor health outcomes, a logistic regression analysis was conducted. Results: Problems with poor health, social trust and finances were found for all three types; however, more similarities than differences were found. The results of the regression model were ambiguous; it is not clear which independent measures contributed the most to poor outcomes. People with USH3 tended to report the most problems regarding the dependent outcome measures. Conclusions: The observations of the associations between the independent variables and poor health, social trust and finances made in the present study are important to bear in mind in a rehabilitation setting; however, they do not fully explain how people with USH actually feel or rate their health. More research is needed to confirm the knowledge that exists within the clinical setting and the life stories told by the people with USH to merge existing knowledge into a rehabilitation setting based on evidence.